2006
DOI: 10.2975/29.2006.274.281
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an oral health promotion program for people with psychiatric disabilities.

Abstract: Oral health programs for people with psychiatric disabilities are rare. This study examined the feasibility efficacy of an oral health intervention for people with psychiatric disabilities. Fifty individuals were recruited and randomly assigned to receive education, reminder system and mechanical toothbrush or just the mechanical toothbrush. 42 completed the study. Plaque index scores recorded at baseline and after 4 weeks indicate a statistically significant improvement for both groups but those in the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 26 publications
4
57
0
Order By: Relevance
“…Lower education suggests a lack of information on general and oral health, while lower monthly income provides fewer opportunities for maintaining oral health care and prevention. Our results support the findings demonstrating that individuals with psychiatric disabilities are often deprived of dental care due to financial problems or lack of dental insurance (22). We found that factors of psychiatric disease taken together significantly predicted the PI values, but none of them alone was a significant predictor.…”
Section: Discussionsupporting
confidence: 82%
“…Lower education suggests a lack of information on general and oral health, while lower monthly income provides fewer opportunities for maintaining oral health care and prevention. Our results support the findings demonstrating that individuals with psychiatric disabilities are often deprived of dental care due to financial problems or lack of dental insurance (22). We found that factors of psychiatric disease taken together significantly predicted the PI values, but none of them alone was a significant predictor.…”
Section: Discussionsupporting
confidence: 82%
“…The primary preventive effort has to focus on tooth brushing: educational instruction and motivation for able people and supportive instruction for nurses to provide or assist dependent patients in their daily oral hygiene. Mechanical toothbrush has proved to be effective for psychiatric patients [30]. …”
Section: Discussionmentioning
confidence: 99%
“…A study performed in the US, in Missouri, demonstrates the efficacy of such programmes, at least in terms of short-term improvements in oral hygiene. 28 Policy-makers should consider providing free, accessible dental care for people with severe mental illness. Examples include the 'Dental as Anything' programme in Melbourne, which offers a collaborative outreach dental service to people with severe mental illness; 13 and elsewhere in Australia, Queensland's strategy to improve the physical health of people with severe mental illness, 'Activate: Mind & Body', promotes oral hygiene and regular care from a dentist.…”
Section: Discussionmentioning
confidence: 99%